(untitled) (Research, Society and Development, 2023)
The objective of this work was to evaluate the technological quality and adaptability in the industrial processing of carioca bean cultivar ANfc9, from two producing regions. Physical parameters were evaluated in fresh beans and quality parameters in canned beans with and without prior hydration in industrial processing. Descriptive analysis was performed for the data obtained and, through analysis of variance, the effects of the place of production (Mato Grosso e Paraná) and type of process (with and without prior hydration) were evaluated. The industrial processing was carried out at Indústria e Conservas Oderich, in the municipality of Orizona -– GO, followed by the unit operations of the industrial plant. The highest levels of technological quality in the grains were from Cascavel-PR, the in natura grain is the most indicated process. The evaluated production sites did not significantly influence the quality of the industrially processed product.